Current distortion mitigation in grid-connected Vienna rectifier during nonunity power factor operation - Molligoda, Devinda A. (2021)
The Vienna rectifier is an attractive converter solution due to the three-level voltage generation and its simple structure. When the Vienna rectifier operates with nonunity power factor, the reference voltage and the input current have different signs during some intervals around the current zero crossings. This creates low-frequency distortion in the current waveforms. One of the preferable methods to reduce this distortion is the zero sequence injection which, however, risks the converter entering into overmodulation. This paper analyses the above distortion and introduces the operation of the Vienna rectifier in two modes, which includes injecting a proper zero sequence and reactive power compensation. This allows the converter to operate in a wide range of power factors without constraining the modulation index. The required reactive current is obtained analytically from the instantaneous values of the converter at any operating point.